TEACHING SPEAKING REPORT TEXT THROUGH VIDEO - Desy Hardiyanti (Universitas Islam Ogan Komering Ilir Kayuagung, 2017)
Speaking is important because it has a function that covers many aspects of human interaction. A video is one of the media that can be used to improve students’ speaking achievement. The objective of this study was to find out whether or not there was a significant difference in speaking achievement between the students who were taught through video and that of those who were not. In this study, quasi-experimental was used. Only the experimental group received the treatment (Creswell, 2003, p.19). The population of this study was all the Eleventh Grade Students of SMA Negeri 2 Tanjung Raja. Therefore, the sample was chosen by using a purposive sample. A t-test was used to analyze the data. Based on the analysis of the data, the value of the t-obtained was 5.271 at the significant level p<0.05 in two-tailed testing with df = 62 the critical value of t-table =1.9990. Since the value of t-obtained was higher than the critical value of t-table, Ho was rejected and Ha was accepted. It meant that there was a significant difference between speaking achievement of the students who were taught through video and those who were not